Understanding the Impact of the Pain Experience on Aboriginal Children's Wellbeing: Viewing through a Two-Eyed Seeing Lens - Latimer, Margot; Simandl, Danielle; Finley, Allen; Rudderham, Sharon; Harman, Katherine; Young, Shelley; MacLeod, Emily; Hutt-MacLeod, Daphne; Francis, Julie (First Peoples Child & Family Review, 2014)
Pain is a universal experience all humans share but can be unique in how it is expressed. The pain experience is influenced by several dynamic factors, including family, community and culture. When it comes to pain expression children are among the most vulnerable often due to difficulty conveying their discomfort. Childhood pain can have significant physical and developmental effects that can last into adulthood. These negative health outcomes may be more pronounced in Aboriginal children given (a) the high prevalence of painful conditions, (b) potential cultural differences in pain expression, (c) the lack of culturally relevant reliable pain assessment approaches; (d) the subsequent shortcomings in pain care resulting in persistent pain (e) impact on wellbeing and untreated childhood pain. Standardized pain scales are based on Western ways of interpreting pain and may not capture the complexities of this experience through Indigenous understandings. Integration of both Western and Indigenous knowledge is accomplished when employing a Two-Eyed Seeing approach which utilizes the best of both Indigenous and Western knowledge. We want to establish reliable means for Aboriginal children to convey pain and hurt from a holistic perspective. By using a Two-Eyed Seeing lens to examine these issues, we hope to learn how to improve health care encounters, reduce hurt and enrich the wellbeing of Aboriginal children.